2019
DOI: 10.1186/s12870-019-1821-z
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic comparison between developing seeds of yellow- and black-seeded Brassica napus reveals that genes influence seed quality

Abstract: Background: Brassica napus is of substantial economic value for vegetable oil, biofuel, and animal fodder production. The breeding of yellow-seeded B. napus to improve seed quality with higher oil content, improved oil and meal quality with fewer antinutrients merits attention. Screening the genes related to this phenotype is valuable for future rapeseed breeding.Results: A total of 85,407 genes, including 4317 novel genes, were identified in the developing seeds of yellow-and black-seeded B. napus, and yellow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 81 publications
5
30
0
Order By: Relevance
“…And apart from B. oleracea, almost no difference in transcript expression level of 4CL5 was found between purple and green leaves (Mushtaq et al, 2016). The 4CL gene played an important role in the pathways of lignin biosynthesis (Jiang et al, 2019).The down-regulated 4CL in our study may decrease the lignin biosynthesis and increase anthocyanin biosynthesis. Surprisingly, the most significant typical pathways between the purple and green leaves were the plant-pathogen interaction, alpha-linolenic acid metabolism, plant hormone signal transduction, and linoleic acid metabolism.…”
Section: Discussionmentioning
confidence: 46%
“…And apart from B. oleracea, almost no difference in transcript expression level of 4CL5 was found between purple and green leaves (Mushtaq et al, 2016). The 4CL gene played an important role in the pathways of lignin biosynthesis (Jiang et al, 2019).The down-regulated 4CL in our study may decrease the lignin biosynthesis and increase anthocyanin biosynthesis. Surprisingly, the most significant typical pathways between the purple and green leaves were the plant-pathogen interaction, alpha-linolenic acid metabolism, plant hormone signal transduction, and linoleic acid metabolism.…”
Section: Discussionmentioning
confidence: 46%
“…Considering that only DFR , LODX , BAN , TT19 and AHA10 in the flavonoid biosynthesis pathways contain cis‐regulatory motifs that can be directly targeted by TT8‐involved complexes (Xu et al , ), the broad suppression of phenylpropanoid/flavonoid biosynthesis genes may be the outcome of unknown regulatory mechanisms in rapeseed. Recently, two transcriptomic studies also found that these down‐regulated DEGs in yellow‐seeded coats were enriched in phenylpropanoid and flavonoid biosynthesis in resynthesized yellow‐seeded rapeseed as research materials (Hong et al , ; Jiang et al , ). Although the causal gene underlying the yellow‐seeded trait is still not clear in their materials, the two functional copies of BnTT8 were significantly down‐regulated in yellow seed compared with black seed in both cases (Hong et al , ; Jiang et al , ).…”
Section: Discussionmentioning
confidence: 97%
“…Recently, two transcriptomic studies also found that these down-regulated DEGs in yellow-seeded coats were enriched in phenylpropanoid and flavonoid biosynthesis in resynthesized yellow-seeded rapeseed as research materials (Hong et al, 2017;Jiang et al, 2019). Although the causal gene underlying the yellow-seeded trait is still not clear in their materials, the two functional copies of BnTT8 were significantly down-regulated in yellow seed compared with black seed in both cases (Hong et al, 2017;Jiang et al, 2019). It is reasonable to postulate that BnTT8 is involved in the downregulation of these DEGs in phenylpropanoid and flavonoid biosynthesis pathways directly or indirectly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Removing these contaminants is a critical step, as RNA with high purity and integrity is critical for gene expression analyses. Although there are several methods available for seed RNA extraction (Kanai et al, 2017;Pereira et al, 2017;Mornkham et al, 2013;Suzuki et al, 2004); fewer protocols are available for the extraction of good quality RNA from specific seed tissue types, especially for the seed coat (Jiang et al, 2019;Liao et al, 2019;Hong et al, 2017;Kour et al, 2014).…”
Section: Introductionmentioning
confidence: 99%